Potential future for SRM and SyncRM in automotive applications - Horváth, Péter István; Jálics, Károly (Design of Machines and Structures, 2022)
The global warming is affecting the life of all of us. Several sectors are contributing to the greenhouse emission. One of the larger contributors is the transportation, in which the road transport accounts for the CO2 emission with a significant percentage. In order to reduce the CO2 emission vehicles are becoming hybridized, electrified. Currently in the electrical vehicles the Permanent Magnet Synchronous Machines (PMSM) outweigh other types of electric motors. The application of the electric machines with rear-earth material is becoming more and more difficult, and costly. Also, the technological improvements of other types of electric machines make them potential candidates to replace the PMSM. As a potential alternative the Switched Reluctance (SRM) and the Synchronous Reluctance Machines (SyncRM) can be considered. The application of such electric machines without permanent magnet would further contribute to the reduction of the greenhouse emissions considering the well-to-wheel cycle. The goal of the following review is to summarize the sectors that have major impact on the CO2 emission, summarize the current trends followed in order to reduce the CO2 emission in the road transport sector, review why the currently preferred PMSM electric motors might have limitations in automotive applications in the future, and review why and how the SRM and SyncRM could be alternative solutions for the PMSM, which is finally summarized in a datum method based comparative evaluation.